2015
DOI: 10.1016/j.jsha.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Objective and subjective image quality with prospectively gated versus ECG-controlled tube current modulation using 256-slice computed tomographic angiography

Abstract: Although prospective ECG-triggered axial scanning increased image noise, it maintained subjective image quality and was associated with a 59% reduction in radiation exposure when compared with ECTCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The radiation exposure in our study was significantly lower in the FLASH protocol than in the prospective protocol. In general, the radiation exposure can be lowered using different techniques, such as ECG-triggered high-pitch spiral scan and prospective ECG-triggered axial scan [19], [20], [21], minimizing the field of scanning guided by calcium score images and reducing the tube voltage when possible. SAS is an acquisition technique associated with low radiation exposure, and several studies have shown that it allows a significant reduction of the radiation exposure without the loss of image quality and diagnostic accuracy [22], [5], [21].…”
Section: Discussionmentioning
confidence: 99%
“…The radiation exposure in our study was significantly lower in the FLASH protocol than in the prospective protocol. In general, the radiation exposure can be lowered using different techniques, such as ECG-triggered high-pitch spiral scan and prospective ECG-triggered axial scan [19], [20], [21], minimizing the field of scanning guided by calcium score images and reducing the tube voltage when possible. SAS is an acquisition technique associated with low radiation exposure, and several studies have shown that it allows a significant reduction of the radiation exposure without the loss of image quality and diagnostic accuracy [22], [5], [21].…”
Section: Discussionmentioning
confidence: 99%
“…Image noise was determined as the standard deviation (SD) of the CT attenuation of a 1-cm 2 circular region of interest placed in the aortic root at the level of the left main coronary artery [12]. The average SD of three sequential slices was taken.…”
Section: Methodsmentioning
confidence: 99%
“…Image quality was scored visually by two observers using the 4-point scoring system, where 4 = excellent image quality; 3 = good quality; 2 = acceptable; 1 = poor nondiagnostic images [12]. The final score was averaged.…”
Section: Methodsmentioning
confidence: 99%
“…When a new protocol or technique is implemented in CCTA, the image quality is an important subject matter to be discussed including the sensitivity and specificity tests to detect particular diseases and the measurements of qualitative and quantitative assessment. Several studies comparing different CT technical parameters emphasized that the image quality has to be at the optimum level for diagnosis (13)(14)(15)(16)(17)(18). However, both qualitative and quantitative image quality were not discussed by some authors in terms of gender differences (16,17).…”
Section: Original Articlementioning
confidence: 99%